2020
DOI: 10.1186/s12893-020-00754-3
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after aortic aneurysm repair in patients with history of cancer: a nationwide dataset analysis

Abstract: Background: Synchronous cancer in patients with abdominal aortic aneurysm (AAA) increases morbidity and mortality after AAA repair. However, little is known about the impact of the history of cancer on mortality after AAA repair. Methods: Patients with intact AAA who were treated with endovascular aneurysm repair or open surgical repair were selected from the Health Insurance and Review Assessment data in South Korea between 2007 and 2016. Primary endpoints included the 30-and 90-day mortality and long-term mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(27 reference statements)
2
1
0
Order By: Relevance
“…Another interesting finding of our study was that a medical history of cancer resulted in a 2.5 fold increase in risk for long-term mortality. A long-term outcome study of AAA patients, by Ahn et al documented that mortality was significantly higher in patients with a history of malignancy [16]. The rate of cancer was four times higher in the long-term mortality group compared to the survivors group in the current study.…”
Section: Discussionsupporting
confidence: 49%
“…Another interesting finding of our study was that a medical history of cancer resulted in a 2.5 fold increase in risk for long-term mortality. A long-term outcome study of AAA patients, by Ahn et al documented that mortality was significantly higher in patients with a history of malignancy [16]. The rate of cancer was four times higher in the long-term mortality group compared to the survivors group in the current study.…”
Section: Discussionsupporting
confidence: 49%
“…Another interesting nding of our study was that the presence of malignancy resulted in a 5 fold increase in risk for long-term mortality. A long-term outcome study of AAA patients, by Ahn et al documented that mortality was signi cantly higher in patients with a history of malignancy [17]. The rate of malignancy was four times higher in the long-term mortality group compared to the survivors group in the current study.…”
Section: Discussionsupporting
confidence: 48%
“…It has been reported that an EVAR or OSR in AAA patients with concomitant cancer, has a poor outcome and that AAA patients with a history of cancer undergoing repair have a mortality rate higher than those without any cancer history (21.21% vs. 17.08%, HR = 1.31, 95% CI: 1.17–1.46, p < 0.0001) [ 36 ]. In our cohort of cancer-free AAA patients, surgical treatment (EVAR or OSR) improved survival compared to NOP patients, but not significantly (58% mortality in EVAR + OSR vs. 67% in NOP p = 0.67).…”
Section: Discussionmentioning
confidence: 99%